(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Daniel Weissbort, one of the anthology’s two editors, participated in "literary translation workshops" at Iowa University and elsewhere in the 1960s. These courses combined poetry and translation through attentive reading and creative writing to recreate each poem’s uniqueness (somewhat in the spirit of the New Criticism). Such a quest is far from the "scholarly" goal of formalizing or explaining translational choices using broad models, categories, or theories.